Clinical patterns associated with the concurrent detection of anti‐HBs and HBV DNA. Issue 2 (26th September 2017) - Anastasiou, Olympia E.; Widera, Marek; Korth, Johannes; Kefalakes, Helenie; Katsounas, Antonios; Hilgard, Gudrun; Gerken, Guido; Canbay, Ali; Ciesek, Sandra; Verheyen, Jens
Abstract : Simultaneous detection of anti‐HBs and HBV DNA is a rare serological combination and has been described in acute and chronic HBV infection. To scrutinize viral and clinical patterns associated with concurrent detection of anti‐HBs and HBV DNA. Simultaneous detection of anti‐HBs and HBV DNA was observed in 64/1444 (4.4%) patients treated for HBV infection at the University Hospital of Essen from 2006 to 2016 (8 with acute, 20 with reactivated, and 36 chronic HBV infection). Clinical data and laboratory parameters were analyzed. Regions of the small hepatitis B surface antigen (SHB) and the reverse transcriptase (RT) were sequenced using next generation sequencing (NGS). Among the 64 patients with detectable HBV DNA and anti‐HBs, 17 were HBsAg negative (HBsAg[−]), and two had acute liver failure. Patients with acute HBV infection had fewer genotype specific amino acid substitutions in the SHB region than patients with reactivated HBV infection (4 [4.5] vs 9 [16.25], P  = 0.043). However, we could observe a significantly higher number of mutations in the a‐determinant region when comparing chronically infected patients to patients with acute infection (0 [1] vs 1 [1], P  = 0.044). The ratio of nonsynonymous to synonymous mutations (Ka/Ks) was on average >1 for the SHB region and <1 for the RT region. The Ka/Ks ratio (>1) in the SHB region indicates that anti‐HBs might have exerted selection pressure on the HBsAg. In three cases the diagnosis of acute HBV infection would have been at least delayed by only focusing on HBsAg testing.